Case study for optimum techno-economic integration of PV and anaerobic digestion for sustainable agri-business. (November 2022) - Amer, Motaz; Mito, Mohamed; Essam, Ahmed; Bayoumi, Seif
Abstract: Adopting unsustainable farming strategies and practices in Egypt led to several socio-economic and environmental problems that are strongly reflected in human health and lifestyle. An example of these problems in the livestock sector is insufficient meat production leading to the dependence on imported meat or cattle. This is in addition to the pollution caused by the unprocessed and wasted cattle manure. To develop the livestock sector in Egypt researchers must introduce new energy solutions to farmers and smallholders. This paper aims to economically compare Photovoltaic (PV) to Anaerobic Digestion (AD) projects' benefits within the livestock sector in Egypt, considering their Life Cycle Costs (LCC) and other parameters using systems components available in the local market. The study proves that the electricity load is the main reason for using either PV or AD. A real case study of a livestock farm is considered to determine its energy profile. Later on, an optimization procedure is implemented for hybrid PV/AD power supplies to optimize the Cost of Energy (CoE) and guarantee a continuous power supply depending on the best use of land and cattle number covered within the comparison. The results show that the CoE produced from renewables is still higher than the CoE from the grid. Furthermore, the rated tariff set by the government to buy electricity from investors will never attract farmers and smallholders to invest in renewables in case of consistent grid power. In other words, farmers under these conditions would only invest in renewables in case a power outage threatens their businesses.